Genomic Landscape in Prostate Cancer in a Latin American Population - Angel, M (2024)
PURPOSEThis study aims to describe genomic characteristics of patients with metastatic prostate cancer (mPC).PATIENTS AND METHODSThis study is a retrospective, multicenter cohort study of patients with mPC and reports on genomic testing. Patients were included from 12 academic centers in five countries.RESULTSA total of 349 patients with PC were included in this study. Most patients (209, 59.9%) were de novo metastatic. Genomic analysis was performed in 233 (66.6%) patients in the metastatic castration-resistant prostate cancer (mCRPC) setting, and only 115 (32.8%) patients had a tumor evaluation in the metastatic hormone sensitive prostate cancer scenario. The evaluation of somatic and/or germline mutations was performed through multigene panel analyses in 290 (83.09%) patients, and next-generation sequencing of BRCA1 and BRCA2 genes was performed in 59 (16.91%) patients. Analyzing the mCRPC subgroup, with a median follow-up of 15.6 months (IQR, 14-19.06), the median progression-free survival (PFS) was not reached (NR) and the PFS at 16 months was 58.7% (95% CI, 50.8 to 67.8). When comparing patients with BRCA mutations with those who are not BRCA-mutated in the mCRPC scenario, the median PFS was NR (95% CI, 14 to NR) and 26.3 months (95% CI, 16.7 to 36.5; P =.2), respectively. Two of six patients with BRCA mutations were treated with targeted therapies (poly-ADP-ribose polymerase inhibitors).CONCLUSIONOur study, to the best of our knowledge, represents one of the larger data sets for somatic testing in patients with PC in Latin America (LATAM). It adds valuable information to the growing body of knowledge about the genomic landscape of advanced PC in real-world daily practice scenarios in LATAM countries, which are not always well-represented in large-scale randomized clinical trials. © 2024 by American Society of Clinical Oncology.